2019
DOI: 10.1088/1361-6463/ab50ed
|View full text |Cite
|
Sign up to set email alerts
|

Three-phases Fe3O4@TiO2-P(VDF-HFP) composite films with high energy storage density at low filler fraction under low operating electric field

Abstract: An enhanced energy storage ability, under a low operating electric field, was achieved in Fe3O4@TiO2-P(VDF-HFP) composite films. The low conductivity TiO2 layer was coated onto the high polarization Fe3O4 to construct Fe3O4@TiO2 core–shell fillers for decreasing filler fraction and alleviating conductivity contrast. For instance, the 2 vol.% Fe3O4@TiO2-P(VDF-HFP) film shows a discharged energy density and energy efficiency of 8.6 J cm−3 and 61.7%, respectively, under a low operating electric field of 261.9 kV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Moreover, the breakdown strength of ( x vol % TO NWs/TNA)–PVDF composites greatly improved in comparison with that of pure PVDF and TNA–PVDF composite (Figure S3), especially for the (5 vol % TO NWs/TNA)–PVDF composite, whose breakdown strength (513 MV/m) is nearly 1.5 times higher than that of the TNA–PVDF composite (330 MV/m). Similar results are further proved by the leakage current behavior of the ( x vol % TO NWs/TNA)–PVDF composites as shown in Figures d and S4. ,, The greatly improved breakdown strengths of ( x vol % TO NWs/TNA)–PVDF composites are contributed by the following reasons: (i) the uniform distribution of TO NWs in the upper layer acts as the scattering center of charges and obstacles in the process of electrical trees, leading to the increased tortuosity of the breakdown path and enhancement of breakdown strength. ,, It should be noted that the 5 vol % fraction is optimal in this study. Since 3 vol % is relatively low, it is less helpful to increase the curvature of breakdown path, resulting in lower breakdown strength, while for the (7 vol % TO NWs/TNA)–PVDF composite, the breakdown strength is greatly decreased owing to the aggregation of the TO NWs, which is in agreement with many previous reports. ,,, (ii) Due to the large dielectric contrast, the redistribution of the electric field that is mainly concentrated in the upper layer helps to protect the bottom layer from being premature breakdown at low electric field.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Moreover, the breakdown strength of ( x vol % TO NWs/TNA)–PVDF composites greatly improved in comparison with that of pure PVDF and TNA–PVDF composite (Figure S3), especially for the (5 vol % TO NWs/TNA)–PVDF composite, whose breakdown strength (513 MV/m) is nearly 1.5 times higher than that of the TNA–PVDF composite (330 MV/m). Similar results are further proved by the leakage current behavior of the ( x vol % TO NWs/TNA)–PVDF composites as shown in Figures d and S4. ,, The greatly improved breakdown strengths of ( x vol % TO NWs/TNA)–PVDF composites are contributed by the following reasons: (i) the uniform distribution of TO NWs in the upper layer acts as the scattering center of charges and obstacles in the process of electrical trees, leading to the increased tortuosity of the breakdown path and enhancement of breakdown strength. ,, It should be noted that the 5 vol % fraction is optimal in this study. Since 3 vol % is relatively low, it is less helpful to increase the curvature of breakdown path, resulting in lower breakdown strength, while for the (7 vol % TO NWs/TNA)–PVDF composite, the breakdown strength is greatly decreased owing to the aggregation of the TO NWs, which is in agreement with many previous reports. ,,, (ii) Due to the large dielectric contrast, the redistribution of the electric field that is mainly concentrated in the upper layer helps to protect the bottom layer from being premature breakdown at low electric field.…”
Section: Resultssupporting
confidence: 70%
“…Similar results are further proved by the leakage current behavior of the (x vol % TO NWs/TNA)−PVDF composites as shown in Figures 4d and S4. 5,35,46 The greatly improved breakdown strengths of (x vol % TO NWs/TNA)−PVDF composites are contributed by the following reasons: (i) the uniform distribution of TO NWs in the upper layer acts as the scattering center of charges and obstacles in the process of electrical trees, leading to the increased tortuosity of the breakdown path and enhancement of breakdown strength. 13,25,47 It should be noted that the 5 vol % fraction is optimal in this study.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the application of polymer as dielectric materials in power grid has effectively improved the performance of power equipment, such as energy storage characteristics [1], [2], mechanical properties [3], electrical strength [4], [5] and so on. Many studies have shown that, on the basis of ensuring the original properties of the above polymeric dielectric materials, nano-fillers can further improve the properties of the materials through effective combination with the polymer matrix [6]- [8].…”
Section: Introductionmentioning
confidence: 99%
“…Reports are available with PVDF-HFP films being prepared by solvent casting method using either mixture of solvents or single solvent. Majority of the times, researchers have either utilized DMF alone [32][33][34][35] or combined DMF and Acetone mixture [36,31] to prepare PVDF-HFP film without a proper comparison of the results obtained from the two. Thus, suitability of the solvent is not found in the literature.…”
Section: Introductionmentioning
confidence: 99%